The Advancement of Learning - Bacon, Francis 1561-1626; Kitchin, G. W. 1827-1912 (London Dent, 1962)
The Advancement of Learning (full title: Of the Proficience and Advancement of Learning, Divine and Human) is a 1605 book by Francis Bacon. It inspired the taxonomic structure of the highly influential Encyclopédie by Jean le Rond d'Alembert and Denis Diderot, and is credited by Bacon's biographer-essayist Catherine Drinker Bowen with being a pioneering essay in support of empirical philosophy.
Keywords: 17th Century (1601-1700); Philosophy; Empiricism; Science